Enhancing CZTS solar cell parameters using CZTSe BSF layer and non-toxic SnS2/In2S3 buffer layer. (2022) - Rachidy, C.; Hartiti, B.; Touhtouh, S.; Moujoud, S.; Faddouli, A.; Belhora, F.; Ertugrul, M.; Fadili, S.; Stitou, M.; Thevenin, P.; Hajjaji, A.
Abstract: Direct bandgap, high absorption coefficient and good electronic properties are the main reasons why the quaternary semiconductor Copper Zinc Tin Sulphide (shortly named CZTS) reached a high interest in the minds of researchers. In this work, a numerical modeling of CZTS solar cells using SCAPS-1D was executed investigating two major points. One, the possibility of replacing the traditional and toxic CdS as buffer layer for CZTS cells, we suggested both Tin sulphide (SnS2 ) and Indium sulphide (In2 S3 ) as they showed good conductivity, optical transparency and optimal bandgap which make them appropriate to be buffer layer materials. Two, the enhancement that could be brought in by adding a back surface field (BSF) in-between the absorber layer and the back contact of the cell, and here we suggested CZTSe for its good optoelectronic properties, nontoxicity, earth-abundant components. The substrate cell configuration Mo/CZTSe/CZTS/(SnS2 and In2 S3 )/ZnO/FTO is used to observe the effect of temperature, absorber, buffer, BSF layer thicknesses, absorber's concentration of acceptors, series resistance and back contact on the cell performance and to optimize the results following a valid procedural approach. Efficiencies of 32, 55% and 32, 50% are reached for SnS2 and In2 S3 respectively. These simulation results could be very helpful to improve our knowledge of this type of solar cells and thus control better the fabrication process.